Advances in Clinical Oncology Research on 99mTc-3PRGD2 SPECT Imaging - Xiao, Liming; Xin, Jun (Frontiers in Oncology, 2022)
The integrin alpha(α)v beta(β)3 receptor is ubiquitous in malignant tumors and has a certain level of specificity for tumors. Technetium-99m hydrazinonicotinamide-dimeric cyclic arginyl-glycyl-aspartic acid peptide with three polyethylene glycol spacers (99mTc-3PRGD2) can bind specifically to the integrin αvβ3 receptor with high selectivity and strong affinity. Thus, it can specifically mark tumors and regions with angiogenesis for tumor detection and be used in single-photon emission computed tomography (SPECT) imaging. This modality has good application value for diagnosing and treating tumor lesions, such as those in the lung, breast, esophagus, head, and neck. This review provides an overview of the current clinical research progress of 99mTc-3PRGD2 SPECT imaging for tumor lesions, including for the diagnosis and differential diagnosis of tumors in different body parts, evaluation of related metastases, and evaluation of efficacy. In addition, the future clinical application prospects and possibilities of 99mTc-3PRGD2 SPECT imaging are further discussed.